Modelli e specchi, mode e tendenze. Esercizi di decostruzione e ricostruzione per l’antropologia italiana - Francesco Faeta (EtnoAntropologia)
Starting  from a tight analysis around the contemporary legitimacy of the notion of Italian anthropology, the Author explores some of the recurring features of this tradition of study, highlighting the limits and lacks, for outlining then topicss that characterize the specific national reflection and indicate some of the paths out of the crisis of credibility from which the overall discipline seems to be, nowadays, plagued.